GC-MS metabolomic approach to study antimicrobial activity of the marine sponge-derived fungi Trichoderma reesei TV221 - Putu Oka Samirana, Yosi Bayu Murti, Riris Istighfari Jenie, Erna Prawita Setyowati (Journal of Applied Pharmaceutical Science, 2023)
One of the fungi associated with the sponge Stylissa flabelliformis, namely Trichoderma reesei TV221, has been known to have antibacterial activity against Gram-positive and Gram-negative bacteria, but the active compound that plays a role is unknown. The aim of the study is to identify antimicrobial compounds from the fungus T. reesei TV221 through the gas chromatography-mass spectroscopy (GC-MS) metabolomic approach. Fungi T. reesei TV221 were cultured on a fermentation medium with various levels of Dextrose and salinity. After 12 days of fermentation, the supernatant and biomass were extracted from each variation of the fermentation medium by employing ethyl acetate as solvent. A total of 18 extracts were examined for antimicrobials against Staphylococcus aureus American type culture collection (ATCC) 25923 and Escherichia coli ATCC 25922 by disc diffusion method. Furthermore, the 18 extracts were regulated by GC-MS chemical profile. The antimicrobial activity test results and GC-MS chemical profile data were then statistically evaluated by employing hierarchical cluster analysis (HCA) and principal component analysis (PCA) methods. The supernatant extracts from various medium numbers as 6 (F), 7 (G), 8 (H), and 9 (I) possessed the highest antimicrobial activity. The chemical profile of the GC-MS extract with variations in Dextrose levels was discovered to possess a more varied GC-MS chemical profile pattern than the GC-MS chemical profile pattern on extracts with variations in salinity levels. Based on the metabolomic approach by utilizing HCA and PCA methods, it is estimated that there are three compounds which possess the most potential antimicrobial activity derived from the fungus T. reesei TV221, that is, 1,4-diaza-2,5-dioxobicyclo[4.3.0]nonane; 1,4-diaza-2,5-dioxo-3- isobutyl bicyclo[4.3.0]nonane; 3-benzyl-1,4-diaza-2,5-dioxobicyclo[4.3.0]nonane. A metabolomic approach which combines activity test data and GC-MS chemical profile data is able to predict compounds that play a pivotal role in the antimicrobial activity of the fungus T. reesei TV221.